Evaluation of rapid influenza diagnostic tests for influenza A and B in the tropics. Issue 8 (14th May 2019) - Chong, Yoong Min; Tan, Xiu Hui; Hooi, Poh Sim; Lee, Lu Mei; Sam, I‐Ching; Chan, Yoke Fun
Abstract: Rapid diagnosis of influenza is important for early treatment and institution of control measures. In developing tropical countries such as Malaysia, influenza occurs all year round, but molecular assays and conventional techniques (such as immunofluorescence and culture) for diagnosis are not widely available. Rapid influenza diagnostic tests (RIDTs) may be useful in this setting. A total of 552 fresh respiratory specimens were assessed from patients with respiratory symptoms at a teaching hospital in Kuala Lumpur, Malaysia from November 2017 to March 2018. Two digital immunoassays (DIAs), STANDARD F Influenza A/B Fluorescence Immunoassay (STANDARD F) and Sofia Influenza A + B Fluorescence Immunoassay (Sofia) and one conventional RIDT (immunochromatographic assay), SD Bioline Influenza Ag A/B/A(H1N1) Pandemic rapid test kit (SD Bioline) were evaluated in comparison with a WHO‐recommended reverse transcription quantitative PCR (RT‐qPCR). Of the 552 samples, influenza A virus was detected in 47 (8.5%) and influenza B virus in 7 (1.3%). The digital immunoassays STANDARD F and Sofia had significantly higher overall sensitivity rates (71.7% and 70.6%, respectively) than the conventional RIDT SD Bioline and immunofluorescence/viral culture (55.8% and 52.8%, respectively). Sensitivity rates were higher for influenza A than influenza B, and specificity rates were uniformly high, ranging from 98% to 100%. Digital readout RIDTs can be used in tropical settings with year‐round influenza if PCR is unavailable.